Isolation and molecular characterization of extended spectrum beta lactamase producing Escherichia coli from chicken meat in Pakistan. - Zainab Liaqat; Ibrar Khan; Sadiq Azam; Yasir Anwar; Eman Hillal Althubaiti; Lalina Maroof (PLoS ONE, 2022)
The goal of this study was to find E. coli, a prevalent pathogen that causes food-borne illnesses, in chicken samples (n = 500) collected from three districts in KhyberPukhtunkhwa: Mardan, Swabi, and Swat. The E. coli isolates were identified by Gram staining, API strips and Universal Stress Protein. A total of 412 samples tested positive for E. coli and were sensitive to MEM, TZP, and FOS as evidenced by disc diffusion method. The isolates were resistant to TE, NOR, and NA with statistically significant results (P≤0.05). The isolates showed the presence of different antibiotic resistance genes; blaOXA-1, blaCTX-M15, blaTEM-1, QnrS, TetA, AAC, AAD, Sul1 and Sul2. The results revealed mutations in blaOXA-1 gene (H81Q), blaTEM-1 (C108Y, T214A, K284E and P301S), QnrS (H95R) and Sul2 (E66A). The findings of this study may be helpful in better management of E. coli infections by physicians.